Reproduction of Relocated and Resident Northern Bobwhites in East Texas - D. Scott Parsons; R. Montague Whiting Jr.; Xiangwen Liu; Brad S. Mueller; Stanley L. Cook (National Quail Symposium Proceedings, 2017)
We examined reproduction by relocated and resident northern bobwhites (Colinus virginianus) on an intensively managed 563-ha study area in Trinity County, eastern Texas. During the late winters of 1990-1992, 155 South Texas (84 hens, 71 cocks) and 136 East Texas (64 hens, 72 cocks) bobwhites were captured, radio-tagged, and relocated to the study area; 139 resident birds (73 hens, 66 cocks) were also captured, radio-tagged, and released at the point of capture. For the 3 years combined, the 33 South Texas, 33 East Texas, and 39 resident hens alive at the beginning of the breeding season produced 6, 13, and 22 documented nests (P = 0.004) and 0, 3, and 4 fledged broods. Pooled, the number of nests by East Texas and resident hens was higher than that of South Texas hens (P = 0.003); numbers of nests of East Texas and resident hens were similar (P = 0.150). Our results do not support relocation of South Texas bobwhites into the East Texas Pineywoods.